2019
DOI: 10.3390/en12030387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Leaching on the Ash Sintering Problems of Wheat Straw

Abstract: Biomass energy has been used for decades in lieu of fossil fuels. However, biomass, such as wheat straw, typically contains a high concentration of alkali elements, which is likely to induce unfavorable conditions during combustion, such as slagging, agglomeration, and corrosion in the boiler. This study investigated the effects of leaching on the chemical compounds and sintering temperatures of wheat straw ash before and after leaching by tap water. Ash melting and sintering degree tests were conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Many researchers carried out straw leaching at different temperatures, from 25 up to 100 °C . Consumption of distilled, deionized or tap water for straw leaching was characterized by water-to-straw ratio, which was from (0.00525–0.024) L/g (Thompson et al), 0.012 L/g (Wu et al), 0.040 L/g (Jenkins et al), 0.050 L/g (Ma et al), and up to 0.065 L/g (Alabdrabalameer et al) . Straw leaching was often conducted without control of leaching completion; measurements of leachate electrical conductivity or water consumption were not reported. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers carried out straw leaching at different temperatures, from 25 up to 100 °C . Consumption of distilled, deionized or tap water for straw leaching was characterized by water-to-straw ratio, which was from (0.00525–0.024) L/g (Thompson et al), 0.012 L/g (Wu et al), 0.040 L/g (Jenkins et al), 0.050 L/g (Ma et al), and up to 0.065 L/g (Alabdrabalameer et al) . Straw leaching was often conducted without control of leaching completion; measurements of leachate electrical conductivity or water consumption were not reported. , …”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to describing the behavior of leached straw ash: measurements of ash composition with calculations changing slagging and fouling indexes, describing the behavior of leached straw ash in energy installation, and determining characteristic temperatures of ash melting behavior . In the last-mentioned paper, it was shown that due to appropriate water leaching, the ash deformation temperature increased from 920 °C for the original straw to 1320 °C for the leached, and for another sample of straw, from 910 to 1250 °C . In study for the sample of original wheat straw, the ash deformation temperature was 1020 °C, and for the ash of water-leached straw it increased only to 1050 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Washing and a thermo-chemical treatment by hydrothermal carbonisation (HTC) have proven to be effective in reducing the amount of alkali metals and Cl in the upgraded biofuels. Therefore they can be applied to control ash-related issues [8][9][10][11][12][13][14][15][16][17]. Both washing and HTC alter the inorganic fuel composition by the dissolution of soluble inorganics in the process water.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of publications on the corrosive influence of biomass concerns the high temperature corrosion of boilers under combustion conditions above 550 • C. The described corrosion processes are related to the activity of potassium and other alkaline metal compounds [25,26] or the presence and activity of fly ash deposits, specific for biomass co-firing [27,28]. Moreover, a number of publications concern surface layers resistant to specific conditions of energy biomass combustion, e.g., [29,30].…”
Section: Introductionmentioning
confidence: 99%